Congenital coronary anomalies in Iraqi adult population - Al-Amiry, Hamid Abdul Wahab; Al-Najjar, Hasan Yousif; Rahman Bairam, Amjad (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Geographic variations in the incidence of different congenital coronary anomalies are well known, but infrequently studied in the Iraqi population.Recognition of coronary anomalies is important in patients undergoing coronary arteriogrphy; coronary interventions and cardiac surgery .Variation in the frequency of primary congenital coronary anomalies may possibly have a genetic background. Patients and methods: Three thousands adult patients underwent diagnostic coronary angiography at two cardiac centers in Baghdad between January 2003 to March 2006. Their angiographic films were reviewed by at least two experts in coronary angiographic study.Results: Among 3000 adult patients who underwent diagnostic coronary angiography, 28(0.93%) patients (16 males, 12 females) had anomalous coronary artery. The mean age was 46±8 years (range from 28-73 years).Twenty four patients (85%) had anomalies of origin and distribution, while the remaining four (15%) had coronary artery fistulae. Abnormal origin of the left circumflex was the most common anomaly, seen in 17(60%) patients. Coronary artery fistula was seen in four patients; from the left anterior coronary artery to the pulmonary trunk in two cases and from the right coronary to the pulmonary trunk in the other cases. Left main stem was absent in four cases (15%).While abnormal origin of the right coronary artery fromthe left circumflex was seen in two cases. Abnormal origin of the right coronary artery from the pulmonary artery was seen in just one case (3.5%). Atherosclerotic plaques in the anomalous artery were seen in four cases (15%) much less than overall case of coronary artery disease in those who underwent coronary angiography (60%).Conclusion: Isolated congenital coronary anomalies in adult is rare and there does not appear to be an increased risk for development of atherosclerosis in anomalouscoronary arteries.